∫ 0 2 π n csc θ d θ = ( Γ ( ϵ n 1 ) ) δ α n 2 β 1 + n 1 Γ ( 1 + n γ )
For ( n > 1 ) .
The above equality holds for real numbers α , β , γ , δ and ϵ . Find ( − 2 3 α β γ δ − ϵ ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
We have (the integral only exists for n > 1 ) ∫ 0 2 1 π csc n 1 θ d θ = 2 1 B ( 2 1 − 2 n 1 , 2 1 ) = 2 Γ ( 1 − 2 n 1 ) Γ ( 2 1 − 2 n 1 ) π = − Γ ( − 2 n 1 ) π n Γ ( 2 1 − 2 n 1 ) and since Γ ( − n 1 ) = 2 π 1 2 − 2 1 − n 1 Γ ( − 2 n 1 ) Γ ( 2 1 − 2 n 1 ) we deduce that the integral is equal to − Γ ( − 2 n 1 ) 2 n π 2 1 + n 1 Γ ( − n 1 ) = Γ ( − 2 n 1 ) 2 n 2 π 2 1 + n 1 Γ ( 1 − n 1 ) Thus α = π , β = 2 , γ = − 1 , δ = 2 , ϵ = − 2 , giving the answer 6 π + 2 .